1978
DOI: 10.1007/bf01915171
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of mixed oxalates

Abstract: The thermogravimetric analysis of several coprecipitated zinc-copper oxalates in nitrogen is reported. The thermal decompositions of these mixed oxalates show a separate single step for dehydration and decomposition in the mass loss versus temperature curve. It is found that the onset temperature decreases with composition. For example, it decreases from 380 ~ for zinc oxalate to 260 ~ for copper oxalate. The end-product is mixed oxides and copper metal. These studies indicate the formation of an interpenetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The temperature sequence of increasing thermal stability may not coincide with the sequence of increasing activation energy values, since it can also depend on the value of the activation entropy [19]. The lack of such a correlation has been observed in the dehydration reactions of EDTA chelates of a number of metal ions [19], and also in the dehydration and decomposition reactions of mixtures of zinc and copper oxblates [20].…”
Section: Kinetics Of Decompositionmentioning
confidence: 94%
“…The temperature sequence of increasing thermal stability may not coincide with the sequence of increasing activation energy values, since it can also depend on the value of the activation entropy [19]. The lack of such a correlation has been observed in the dehydration reactions of EDTA chelates of a number of metal ions [19], and also in the dehydration and decomposition reactions of mixtures of zinc and copper oxblates [20].…”
Section: Kinetics Of Decompositionmentioning
confidence: 94%
“…The double salts ultimately decomposed to metal oxide, alkali metal sulfate, and S03. Coprecipitated Zn-Cu oxalates were subjected to TG in N2 (49) and it was found that decomposition onset temperatures vary with composition, decreasing from 380 °C for ZnC204 to 260 °C for CuC204.…”
Section: Differential Thermal Analysis-dynamic Scanning Calorimetrymentioning
confidence: 99%
“…[11,14] Successful isomorphous substitution by Zn II in Cu II oxalate has been rarely reported in the literature. In the thermal decomposition of ac oprecipitated Cu/Zno xalate (46.2 %C u), Dalvi and Chavan [15] observeda na nomalous single decomposition step, which they attributed to the formation of am etastable solid solution. On applying the oxalate gel/coprecipitation methodt ot he ternary Cu/ZnO/Al 2 O 3 system,D eng et al [6a] reported the formation of the binary mixed-metal oxalate phase from ethanolic solution.…”
Section: Introductionmentioning
confidence: 99%